2019
DOI: 10.3389/fmicb.2019.00704
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Signature Sequences of Bacterial Δ4,5Hexuronate-2-O-Sulfatases

Abstract: Glycosaminoglycan (GAG) sulfatases, which catalyze the hydrolysis of sulfate esters from GAGs, belong to a large and conserved sulfatase family. Bacterial GAG sulfatases are essential in the process of sulfur cycling and are useful for the structural analysis of GAGs. Only a few GAG-specific sulfatases have been studied in detail and reported to date. Herein, the GAG-degrading Photobacterium sp. FC615 was isolated from marine sediment, and a novel Δ 4,5 hexuronate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 54 publications
(75 reference statements)
0
10
0
Order By: Relevance
“…Marine bacterium Photobacterium sp. FC615 [33] was collected from Jiaozhou Bay, near Qingdao city in Shandong province, China. E. coli BL21 (DE3) was used for gene expression and it was cultured at 37 °C in Luria–Bertani (LB) broth or on LB broth agar (LB broth supplemented with 1.5% agar) with ampicillin (100 μg/ml).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Marine bacterium Photobacterium sp. FC615 [33] was collected from Jiaozhou Bay, near Qingdao city in Shandong province, China. E. coli BL21 (DE3) was used for gene expression and it was cultured at 37 °C in Luria–Bertani (LB) broth or on LB broth agar (LB broth supplemented with 1.5% agar) with ampicillin (100 μg/ml).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, two novel alginate lyases, AlyPB1 and AlyPB2, were identified from the draft genome of a marine bacterium, Photobacterium sp. FC615 [33]. AlyPB1 and AlyPB2 were characterized as endolytic and exolytic alginate lyases, respectively, and showed a strong synergistic effect on the complete digestion of alginate.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with exosulfatases, endosulfatases should be more useful enzymatic tools for CS/DS studies but seem to be very rare in nature. Our recent study has shown that CS/DS sulfatases with similar specificities have common signature sequences and can cluster to form a single branch in the phylogenetic tree, although they descended from separate ancestral genes (Wang et al, 2019a). Based on this finding, a series of 4,5 HexA-2-O-sulfatases have been successfully predicted and verified from sequences in GenBank (Wang et al, 2019a), and we believe that some CS/DS endosulfatases could also be found by using this method.…”
Section: Cs/ds Sulfatasesmentioning
confidence: 81%
“…Technically, sulfatases with specific activity that allow them to selectively remove sulfate groups from CS/DS chains should be another important tool for the structural and functional studies of CS/DS. Based on the positions of sulfate groups in CS/DS chains, there are several types of specific sulfatases in animals and bacteria, such as N-acetylgalactosamine-4-O-sulfatase (Yamagata et al, 1968;Sugahara and Kojima, 1996;Wang et al, 2019b;Baum et al, 1959) and N-acetylgalactosamine-6-O-sulfatase (Yamagata et al, 1968;Sugahara and Kojima, 1996;Lim and Horwitz, 1981;Singh et al, 1976), which specifically hydrolyze sulfate groups on the C-4 and C-6 positions of GalNAc residues, respectively, and hexuronate-2-O-sulfatase, which specifically removes C-2 sulfate groups from saturated or unsaturated hexuronic acids derived from the digestion of CS/DS by GAG lyases (Sugahara and Kojima, 1996;Myette et al, 2003;Wang et al, 2019a; Tables 2, 3). Based on the sequence similarities, the GAG sulfatases were recently classified in the database SulfAtlas (http://abims.sb-roscoff.fr/sulfatlas/) ( Barbeyron et al, 2016).…”
Section: Cs/ds Sulfatasesmentioning
confidence: 99%
See 1 more Smart Citation